On the Ranking of Shells and People : Comments on "A Papuan Plutocracy: Ranked Exchange on Rossell Island" - Gregory, Chris (Suomen Antropologi, 2009)
Comments on: JOHN LIEP. A Papuan Plutocracy: Ranked Exchange on Rossel Island. Aarhus: Aarhus University Press, 2009. Pp. 376. ISBN: 978-87-7934-446-4 This is a magnificent piece of scholarship. It has been a lifetime in the making and it shows on every page, in every paragraph and every sentence of this meticulously argued and beautifully produced ethnography. If the ethnographic studies of the Massim can be likened to ndap shells of different rank, then this book will find its way into the very high division where it will circulate alongside the classics such as Malinowksi’s Argonauts and Young’s Fighting with Food. Liep not so much resolves the theoretical controversies about exchange theory that Armstrong’s 1922 book on Rossel Island shell money generated, but dissolves them and raises a whole new set of more interesting questions. Rossel Island has been defined as exceptional in Melanesian studies because of its extraordinarily complicated shell-money system and its exceptionally difficult language that bears no family resemblances with the Austronesian languages found on the neighbouring islands. Insofar as the exchange-system is concerned, Liep convincingly demonstrates that it is a variation on a familiar Oceanic theme. He does this by presenting original data on the rules and practice of Rossel shell-exchange and situating it expertly in a broader comparative perspective. What makes this book especially valuable is that Liep is well aware of its limitations and makes no attempt to hide this. Of course, every ethnographic report is limited to some extent but what sets Liep’s book apart is that he does his best to define precisely the boundaries of his knowledge and understanding. He is careful to distinguish what he knows well from what he is unsure about and what he does not know. What he gives us then are, respectively, persuasive arguments about which there can be little debate, speculative propositions about which reasonable people may disagree, and questions that require more research. I am primarily concerned with the latter two issues here.